2014
DOI: 10.4174/astr.2014.87.4.197
|View full text |Cite
|
Sign up to set email alerts
|

Changes in suprarenal and infrarenal aortic angles after endovascular aneurysm repair

Abstract: PurposeWe investigated whether suprarenal and infrarenal aortic angles change after the endovascular aneurysm repair (EVAR) procedure and during follow-up, and investigated the correlation between infrarenal aortic angle after EVAR and type Ia endoleaks.MethodsData collected on 70 EVAR procedures for a fusiform infrarenal aortic aneurysm performed between May 2006 and December 2012 were supplemented with a retrospective review of charts and radiographs.ResultsThe greater the preoperative infrarenal aortic angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The authors showed a statistically significant change in the mean suprarenal and infrarenal angles by a mean difference of 5°±1° and 8°±2°, respectively (p<0.01). Similarly, Lee et al 9 observed an immediate (1 month) decrease in the supra- and infrarenal angles after EVAR (32.1°±21.6° to 27.0°±17.8° and 43.4°±25.0° to 30.4°±17.6°, respectively). Interestingly, a recent bioengineering study by De Bock et al 10 demonstrated that the suprarenal angle can more adversely influence neck geometry as it was found to correlate with greater asymmetry in the forces distributed over the aortic neck, which is a relative measure of how these forces act to straighten the proximal neck.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…The authors showed a statistically significant change in the mean suprarenal and infrarenal angles by a mean difference of 5°±1° and 8°±2°, respectively (p<0.01). Similarly, Lee et al 9 observed an immediate (1 month) decrease in the supra- and infrarenal angles after EVAR (32.1°±21.6° to 27.0°±17.8° and 43.4°±25.0° to 30.4°±17.6°, respectively). Interestingly, a recent bioengineering study by De Bock et al 10 demonstrated that the suprarenal angle can more adversely influence neck geometry as it was found to correlate with greater asymmetry in the forces distributed over the aortic neck, which is a relative measure of how these forces act to straighten the proximal neck.…”
Section: Introductionmentioning
confidence: 63%
“…Interestingly, Lee et al 9 reported a strong association between the preoperative suprarenal and infrarenal angulation in their study (r=0.72, p<0.001), which included stent-grafts with nitinol-based radial force involving a suprarenal fixation stent (Zenith, Endurant) or not (Excluder). According to their study, the suprarenal aortic angle decreased immediately after EVAR and continued to decrease during the first month, unlike the infrarenal aortic angle that continued to decrease slowly thereafter.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Many researchers reported the disadvantages and poor outcomes of EVAR in the treatment of aneurysms with hostile neck anatomy that did not meet the criteria [ 16 - 18 ]. The neck angle decreased significantly within 1 week after EVAR and then gradually decreased thereafter [ 6 , 7 , 19 ]. When the preoperative neck angle was greater than 60°, it decreased immediately after EVAR [ 19 ].…”
Section: Discussionmentioning
confidence: 99%